3‐D Regional Ionosphere Imaging and SED Reconstruction With a New TEC‐Based Ionospheric Data Assimilation System (TIDAS). Issue 4 (1st April 2022) - Aa, Ercha; Zhang, Shun‐Rong; Erickson, Philip J.; Wang, Wenbin; Coster, Anthea J.; Rideout, William
Abstract: A new TEC‐based ionospheric data assimilation system (TIDAS) over the continental US and adjacent area (20°–60°N, 60°–130°W, and 100–600 km) has been developed through assimilating heterogeneous ionospheric data, including dense ground‐based Global Navigation Satellite System (GNSS) Total Electron Content (TEC) from 2, 000+ receivers, Constellation Observing System for Meteorology, Ionosphere, and Climate radio occultation data, JASON satellite altimeter TEC, and Millstone Hill incoherent scatter radar measurements. A hybrid Ensemble‐Variational scheme is utilized to reconstruct the regional 3‐D electron density distribution: a more realistic and location‐dependent background error covariance matrix is calculated from an ensemble of corrected NeQuick outputs, and a three‐dimensional variational (3DVAR) method is adopted for measurement updates to obtain an optimal state estimation. The spatial‐temporal resolution of the reanalyzed 3‐D electron density product is as high as 1° × 1° in latitude and longitude, 20 km in altitude, and 5 min in universal time, which is sufficient to reproduce ionospheric fine structure and storm‐time disturbances. The accuracy and reliability of data assimilation results are validated using ionosonde and other measurements. TIDAS reanalyzed electron density is able to successfully reconstruct the 3‐D morphology and dynamic evolution of the storm‐enhanced density (SED) plume observed during the St. Patrick's day geomagnetic storm on 17 March 2013 with high fidelity. Using TIDAS, we found that the 3‐D SED plume manifests as a ridge‐like high‐density channel that predominantly occurred between 300 and 500 km during 19:00–21:00 UT for this event, with the F2 region peak height being raised by 40–60 km and peak density enhancement of 30%–50%. Plain Language Summary: Ionosphere data assimilation is an effective technique to provide a valid specification of Earth's ionosphere through assimilating various data to obtain an optimal state estimation. In this study, a new regional ionospheric data assimilation system is constructed using a hybrid Ensemble‐Variational assimilation scheme to incorporate data from multi‐instrument measurements, especially dense ground‐based Global Navigation Satellite System observations. This data assimilation system can provide accurate and reliable three‐dimensional time‐evolving electron density maps over the continental US and adjacent areas with high spatial‐temporal resolution (1° × 1° × 20 km × 5 min). This high‐fidelity regional data assimilation system is a powerful tool to reconstruct localized storm‐time ionospheric morphology with unprecedented and fine‐scale details. Results can help advance current understanding of the fine structures and underlying mechanisms of the midlatitude ionospheric density gradients during space weather events in such structures as storm‐enhanced density plumes. Key Points: A new total electron content‐based ionospheric data assimilation system over the Continental US is developed using a hybrid Ensemble‐Variational scheme Regional 3‐D ionospheric electron density distribution is reconstructed with a high spatial‐temporal resolution (1° × 1° × 20 km × 5 min) 3‐D Morphology and evolution of storm‐enhanced density plume during the 2013 St. Patrick's day geomagnetic storm was successfully reconstructed and reanalyzed